Towards allosteric receptors – synthesis of β-cyclodextrin-functionalised 2,2’-bipyridines and their metal complexes - Kremer, Christopher; Schnakenburg, Gregor; Lützen, Arne (Beilstein Journal of Organic Chemistry, 2014)
Herein, we present three new 2,2’-bipyridines that carry two β-cyclodextrin moieties in different substitution patterns. When coordinated by zinc(II) or copper(I) ions (or their complexes), these compounds undergo conformational changes and switch between “open” and “closed” forms and thereby bringing together or separating the cyclodextrin moieties from each other.
Keywords: allosteric receptors; 2,2’-bipyridines; β-cyclodextrin; supramolecular chemistry; metal complexes

(untitled) - Mammen, M.; Choi, S.-K.; Whitesides, G. M. (Angew. Chem., 1998)
Angew. Chem., Int. Ed. 1998, 37, 2754–2794. doi:10.1002/(SICI)1521-3773(19981102)37:20<2754::AID-ANIE2754>3.0.CO;2-3

(untitled) - Fasting, C.; Schalley, C. A.; Weber, M.; Seitz, O.; Hecht, S.; Koksch, B.; Dernedde, J.; Graf, C.; Knapp, E.-W.; Haag, R. (Angew. Chem., 2012)
Angew. Chem., Int. Ed. 2012, 51, 10472–10498. doi:10.1002/anie.201201114

(untitled) - Whitty, A. (Nat. Chem. Biol., 2008)

(untitled) - Hunter, C. A.; Anderson, H. L. (Angew. Chem., 2009)
Angew. Chem., Int. Ed. 2009, 48, 7488–7499. doi:10.1002/anie.200902490

(untitled) - Ercolani, G.; Schiaffino, L. (Angew. Chem., 2011)
Angew. Chem., Int. Ed. 2011, 50, 1762–1768. doi:10.1002/anie.201004201

Allosteric Regulatory Enzymes - Traut, T. (Springer, 2008)

(untitled) - Rebek, J., Jr (Acc. Chem. Res., 1984)

(untitled) - Tabushi, I. (Pure Appl. Chem., 1988)

(untitled) - Nabeshima, T. (Coord. Chem. Rev., 1996)

(untitled) - Shinkai, S.; Ikeda, M.; Sugasaki, A.; Takeuchi, M. (Acc. Chem. Res., 2001)

(untitled) - Takeuchi, M.; Ikeda, M.; Sugasaki, A.; Shinkai, S. (Acc. Chem. Res., 2001)

(untitled) - Kovbasyuk, L.; Krämer, R. (Chem. Rev., 2004)

(untitled) - Zhu, L.; Anslyn, E. V. (Angew. Chem., 2006)
Angew. Chem., Int. Ed. 2006, 45, 1190–1196. doi:10.1002/anie.200501476

(untitled) - Kremer, C.; Lützen, A. (Chem.–Eur. J., 2013)

(untitled) - Zahn, S.; Reckien, W.; Kirchner, B.; Staats, H.; Matthey, J.; Lützen, A. (Chem.–Eur. J., 2009)

(untitled) - Howard, S. T. (J. Am. Chem. Soc., 1996)

(untitled) - Pan, J.-F.; Chen, Z.-K.; Chua, S.-J.; Huang, W. (J. Phys. Chem. A, 2001)

(untitled) - Lehtonen, O.; Ikkala, O.; Pietilä, L.-O. (J. Mol. Struct.: THEOCHEM, 2003)

(untitled) - Lützen, A.; Haß, O.; Bruhn, T. (Tetrahedron Lett., 2002)

(untitled) - Staats, H.; Eggers, F.; Haß, O.; Fahrenkrug, F.; Matthey, J.; Lüning, U.; Lützen, A. (Eur. J. Org. Chem., 2009)

(untitled) - Staats, H.; Lützen, A. (Beilstein J. Org. Chem., 2010)

Container Molecules and Their Guests - Cram, D. J.; Cram, M. J. (Royal Society of Chemistry, 1994)

(untitled) - Sherman, J. C. (Tetrahedron, 1995)

Cyclodextrins and Their Complexes - Dodziuk, H. (Wiley-VCH, 2006)

(untitled) - Kiehne, U.; Bunzen, J.; Staats, H.; Lützen, A. (Synthesis, 2007)

(untitled) - Hapke, M.; Staats, H.; Wallmann, I.; Lützen, A. (Synthesis, 2007)

(untitled) - Kremer, C.; Lützen, A. (Synthesis, 2011)

(untitled) - Lee, T.; Lim, J.; Chung, I.; Kim, I.; Ha, C.-S. (Macromol. Res., 2010)

(untitled) - Hbaieb, S.; Kalfat, R.; Chevalier, Y.; Amdouni, N.; Parrot-Lopez, H. (Mater. Sci. Eng., C, 2008)

(untitled) - Sallas, F.; Marsura, A.; Petot, V.; Pintér, I.; Kovács, J.; Jicsinszky, L. (Helv. Chim. Acta, 1998)

(untitled) - Schmittel, M.; Lüning, U.; Meder, M.; Ganz, A.; Michel, C.; Hederich, M. (Heterocycl. Commun., 1997)

(untitled) - Schmittel, M.; Ganz, A. (Synlett, 1997)

(untitled) - Schmittel, M.; Ganz, A. (Chem. Commun., 1997)

(untitled) - De, S.; Mahate, K.; Schmittel, M. (Chem. Soc. Rev., 2010)

(untitled) - Lüning, U.; Müller, M. (Chem. Ber., 1990)

(untitled) - Yamada, M.; Nakamura, Y.; Kuroda, S.; Shimao, I. (Bull. Chem. Soc. Jpn., 1990)

(untitled) - Frey, J.; Kraus, T.; Heitz, V.; Sauvage, J.-P. (Chem.–Eur. J., 2007)

(untitled) - Nishimura, N.; Yoza, K.; Kobayashi, K. (J. Am. Chem. Soc., 2010)

(untitled) - Lüning, U.; Abbass, M.; Fahrenkrug, F. (Eur. J. Org. Chem., 2002)

(untitled) - Cacciapaglia, R.; Di Stefano, S.; Fahrenkrug, F.; Lüning, U.; Mandolini, L. (J. Phys. Org. Chem., 2004)

(untitled) - Lüning, U.; Fahrenkrug, F. (Eur. J. Org. Chem., 2004)

(untitled) - Schmittel, M.; Ganz, A.; Fenske, D.; Herderich, M. (J. Chem. Soc., Dalton Trans., 2000)